Pembelajaran Matematika Berpikir Komputasi Materi Pola Bilangan dengan Media Kalkulator Web Berbasis Javascript - Memolo, Tundung (Jurnal Didaktika Pendidikan Dasar, 2022)
Learning mathematics material on number patterns is very relevant in teaching students to think computationally. This study uses a JavaScript-based web calculator media to help students explore their learning. The purpose of this research is to describe the process of learning number patterns using a web calculator media and to find out the percentage of students’ positive responses in computational thinking. This research is a qualitative descriptive. The results showed that (a) most of the students understood pattern recognition, decomposition and abstraction; (b) the average percentage of student responses related to computational thinking: pattern recognition of 82.7%, decomposition of 72.4%, abstraction of 68.9%, while in algorithms of 67.24%; (c) The average computational thinking ability is 72.8%.